Pliushch B. O. Peculiarities of reproduction of the contrast as the main feature of V. Vynnychenko’s idiostyle in the English translation - Pliushch B. O. (Philological Treatises, 2020)
The article deals with the consideration of the English translations of V.Vynnychenko’s small prose. Relying on the complex comparative analysis, the peculiarities of rendering in the English translation of the contrast, the main feature of V.Vynnychenko’s idiostyle, are being analysed.